Nebulized Dexmedetomidine to Reduce Delirium after General Anesthesia Sevoflurane Inhalation in Preschool Children Undergoing Elective Surgery - Wongkar, Jimmy; Kurniyanta, I Putu; Suarjaya, I Putu Pramana; Tjokorda Gde Agung Senapathi; Widnyana, I Made Gede (Newinera Publisher, 2025)
Surgery in children remains a major challenge, particularly due to complications such as post-anesthetic delirium, with an incidence rate of up to 80%, especially in preschool-aged children when sevoflurane is the primary agent. Nebulized dexmedetomidine has been shown to reduce the incidence of post-anesthetic delirium with minimal risk of side effects. This study aims to evaluate the effectiveness of nebulized dexmedetomidine in reducing the incidence of post-anesthetic delirium in preschool-aged children undergoing elective surgery, as part of enhancing recovery after pediatric surgery (ERAPS). This research was a double-blind, randomized controlled trial, involving 72 pediatric patients aged 2–6 years undergoing elective surgery under general anesthesia with sevoflurane. Subjects were randomly divided into two groups; Treatment group receiving nebulized dexmedetomidine 2 mcg/kg (n=36) and Control group receiving nebulized normal saline (n=36). The primary outcome was the incidence of delirium during recovery at 15, 30, 60, and 120 minutes, assessed using the Pediatric Anesthesia Emergence Delirium (PAED) Scale. Statistical analysis revealed a significantly lower incidence of post-anesthetic delirium in the nebulized dexmedetomidine group (19.4%) compared to the control group (52.8%) at 15, 30, and 60 minutes (p<0.05), with a reduction in proportion by 33.4% (p=0.003). Relative risk analysis (RR = 0.427, 95% CI: 0.218–0.835; PF = 0.631) demonstrated that dexmedetomidine provides protective effects and significantly reduces the incidence of post-anesthetic delirium in preschool-aged children undergoing elective surgery with sevoflurane inhalational anesthesia. No side effects requiring intervention were observed during this study.